Ultrasonography of the lung - Radzina, Maija; Biederer, Jürgen (RöFo, 2019)
BACKGROUND: High diagnostic accuracy, increasing clinical experience and technical improvements are good reasons to consider lung ultrasound (US) for the assessment of pleural and pulmonary diseases. In the emergency room and in intensive care, it is well acknowledged, but application in other settings is rare. The aim of this review is to update potential users in general radiology about the diagnostic scope of lung US and to encourage more frequent use of this generally underestimated lung imaging modality. - METHOD: Literature review was done independently by the two authors in MEDLINE (via PubMed) covering a time span from 2002 until 2017 using free text and Medical Subject Headings/MeSH. Article selection for the bibliography was based on consensus according to relevance and evidence. - RESULTS AND CONCLUSION: The technical prerequisites include a standard ultrasound unit with a suitable transducer. Pleural effusion and pneumothorax, atelectasis, interstitial edema, pneumonia, exacerbated chronic obstructive pulmonary disease/asthma and pulmonary embolism can be distinguished by particular ultrasound signs, artifacts and their combinations. A highly standardized selection of access points and terminology for the description of imaging findings contributes to high diagnostic accuracy even in challenging patients and settings. Besides the assessment of acute respiratory failure in the emergency room, lung US may be used for monitoring interstitial fluid accumulation in volume therapy and for the diagnosis of pneumonia or the assessment of pleural effusion and pleurisy in a routine outpatient setting. Last but not least, the increasing concerns about medical radiation exposure warrant a more extensive use of this sometimes underestimated modality as a cost-, time- and radiation-saving alternative or valuable adjunct to the standard imaging modalities. - KEY POINTS: · Lung US is a safe, quick and readily available method with options for dynamic imaging of respiratory function.. · Proper selection of technical parameters customized to the clinical question and standardized terminology for the precise description and interpretation of the imaging signs regarding patient history determine its diagnostic accuracy.. · In dyspnea lung US differentiates pneumothorax, lung edema, pneumonia, pulmonary embolism, atelectasis and pleural effusion.. · In intensive care, lung US allows monitoring of lung ventilation and fluid administration.. · It saves radiation exposure in serial follow-up, in pregnancy and pediatric radiology.. - CITATION FORMAT: · Radzina M, Biederer J, Ultrasonography of the Lung. Fortschr Röntgenstr 2019; 191: 909-923.